2017
DOI: 10.1016/j.pec.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Patient-provider communication in nephrology care for adolescents and young adults

Abstract: During transition-oriented treatment planning, providers should engage both AYAs and caregivers to avoid potential gaps in communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…64,66 Furthermore, collaborations with providers and the healthcare system can significantly decrease barriers that patients and caregivers experience in transition readiness. Increased participation of youth in clinic visits as they get older indicates an appropriate shift in health-information sharing responsibilities 67 and can lead to higher success with transition readiness. 68 In fact, ability to foster connections with healthcare providers and elicit support around transition needs, rather than complete autonomy, is critical in building resilience in transition-age patients.…”
Section: Risk and Resilience Factorsmentioning
confidence: 99%
“…64,66 Furthermore, collaborations with providers and the healthcare system can significantly decrease barriers that patients and caregivers experience in transition readiness. Increased participation of youth in clinic visits as they get older indicates an appropriate shift in health-information sharing responsibilities 67 and can lead to higher success with transition readiness. 68 In fact, ability to foster connections with healthcare providers and elicit support around transition needs, rather than complete autonomy, is critical in building resilience in transition-age patients.…”
Section: Risk and Resilience Factorsmentioning
confidence: 99%
“…The CHAT study examined shifts in communication between patients, family members, and providers during routine clinic visits, and found that caregivers spoke more than adolescents and young adults and shifts in communication occurred at different time points, with caregiver communication decreasing in middle adolescence while adolescent/young adult communication did not increase until young adulthood. This mismatch raises concern for a potential lapse in communication during middle adolescence, which may negatively impact adherence in this vulnerable population 29 …”
Section: Family‐level Factors That Contribute To and Impact Non‐adhermentioning
confidence: 99%
“… 29 , 32 Also, the ages of patients varied from 8 to 17 years, encompassing a range of developmental stages, during which child participation has been shown to evolve. 44 Selection bias might have limited inclusion of less social physicians or families or those with more strained physician-family relationships. Participants were aware that they were being videotaped, thus leading to the possibility of a Hawthorne effect – that participants did not display their typical behavior due to awareness of observation.…”
Section: Limitationsmentioning
confidence: 99%